THE PRINCIPLE OF AVOIDING CONFLICT OF INTEREST IN CASE OF DAMAGE BY TAX AUTHORITIES: THEORETICAL-LEGAL AND COMPARATIVE ANALYSIS - N. А. Abdurakhimov (Modern American Journals, 2026)
This article analyzes the theoretical and legal foundations, practical mechanisms, and international experience of the principle of avoiding conflicts of interest in compensating for damage caused by tax authorities. The article compares the concept of fiduciary obligations, theories of state responsibility, and the experience of Germany and France with the legislation of Uzbekistan.
Keywords: Tax authorities, conflict of interest, state responsibility, fiduciary duties, damages, judicial independence, anti-corruption expertise.